THE ROLE OF GOVERNMENT SUPPORT, GREEN SUPPLY CHAIN MANAGEMENT, AND TECHNOLOGICAL INNOVATION IN ENHANCING MSME COMPETITIVENESS - Purnamasari, Etika; Fitriyasari, Maliatul; Endaryati, Eni; Putra, Johni Eka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The competitiveness of micro, small, and medium enterprises (MSMEs) is shaped by multiple factors, including government support, green supply chain management (GSCM), and technological innovation. This study investigates how these elements influence MSME performance through a quantitative approach, analyzing data collected from MSME owners using multiple regression techniques. The results indicate that government support plays a crucial role by providing financial aid, regulatory ease, and training programs. GSCM adoption significantly enhances operational efficiency and sustainability, while technological innovation drives productivity and market expansion. The study contributes to resource-based and institutional theories by demonstrating the strategic importance of external support and internal capabilities in fostering MSME growth. The findings offer practical implications for policymakers, business owners, and industry stakeholders, emphasizing the need for policy frameworks that promote financial assistance, sustainability, and digital transformation. Future research should incorporate longitudinal methods and broader geographical perspectives to strengthen these insights.